Framework for Transmission Line Fault Detection in a Five Bus System Using Discrete Wavelet Transform - Kumari K, Krishna; Vanitha, V.; G. Hussien, Mohamed (Distributed Generation & Alternative Energy Journal, 2021)
The transmission line is an essential part of the power system and since it is exposed to the harsh environmental conditions, it is susceptible to open circuit and short circuit faults. As the occurrence of failures affect the quality of the electric power supplied, identifying the fault and clearing it quickly is critical for the reliable power system operation. Fault Diagnostics of a multi bus system is crucial for Power system stable operation. In this paper, a ﬁve- bus system is taken up for the study and twelve different types of faults with varying fault durations are applied in transmission lines at different locations. Then Discrete Wavelet Transform (DWT) is applied to the receiving end current signals of the line and derived wavelet coefﬁcients are used to identify the type of fault. Simulation and extraction of wavelet coefﬁcients are done in MATLAB Simulink and results are presented. The Model Developed of a ﬁve Bus system for Fault Diagnostics and Simulation can be used as Framework for Fault Classiﬁcation and Localization. The derived Wavelet Transform proves to be appropriate for the Framework developed.